2013
DOI: 10.1631/jzus.b1300012
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality, anthocyanin and total phenolic contents, and antioxidant activities of 45 blueberry cultivars grown in Suwon, Korea

Abstract: Blueberry fruits from 45 commercial cultivars (39 northern highbush and 6 half highbush blueberry) grown in Suwon, Korea were analyzed for fruit size, soluble solids content, titratable acidity, total anthocyanin content, total phenolic content, and antioxidant activity. Fruit characteristics varied widely among the 45 blueberry cultivars. Fruit weight ranged from 0.9 to 3.6 g, soluble solids content from 8.3 to 14.3 °Brix, and titratable acidity from 0.8% to 3.6%. Antioxidant activity ranged from 0.7 to 2.1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
4
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 27 publications
12
41
4
6
Order By: Relevance
“…Our results correspond with those of Borowska et al [10], who reported the TP content in the fruits of five investigated cranberry cultivars of 192.1-374.2 mg GAE/100 g FM as well as Kim et al [21], who determined 170.9-434.5 mg GAE/100 g FM in fruits of highbush blueberries. Moze et al [22] and Rodrigues et al [23] determined in blueberries significantly higher TP content (1027-1629 mg GAE/100 g FM and 274.5-694.6 mg GAE/100 g FM respectively).…”
Section: Resultssupporting
confidence: 92%
“…Our results correspond with those of Borowska et al [10], who reported the TP content in the fruits of five investigated cranberry cultivars of 192.1-374.2 mg GAE/100 g FM as well as Kim et al [21], who determined 170.9-434.5 mg GAE/100 g FM in fruits of highbush blueberries. Moze et al [22] and Rodrigues et al [23] determined in blueberries significantly higher TP content (1027-1629 mg GAE/100 g FM and 274.5-694.6 mg GAE/100 g FM respectively).…”
Section: Resultssupporting
confidence: 92%
“…In the literature, for blueberry samples at least 170.9 mg and for lingonberry at least 431 mg gallic acid equivalent/100 g fresh fruit were measured after extraction three times with organic or organic containing solvents. In this study only 29.8 and 26.9 mg gallic acid equivalent/100 g fresh blueberry and lingonberry could be detected, respectively (LEE & FINN, 2012;KIM et al, 2013). Same results were expected for ascorbic acid concentrations, when compared to total contents.…”
Section: Resultssupporting
confidence: 70%
“…Total phenolic content was determined by the Folin-Ciocalteu method as described previously (Kim et al, 2013). In brief, appropriate dilutions of extracts (1 ml) were mixed with Folin-Ciocalteu reagent (2 ml).…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%